Family-based association tests: FBATs for various data types - Lange, Christoph (Henry Stewart Talks, 2007)
Childhood asthma management program (CAMP), Multivariate tests, FBAT-GEE, FBATs for time-to-onset data, Time-to-onset data for complex diseases, FBAT logrank and Wilcoxon, Quantitative trait analysis, Quantitative traits for complex diseases, Longitudinal data, FBAT-PC, Estimation of VG and VP, The heritability of the FBAT-PC phenotype, Heritability of the overall phenotype, CAMP: univariate data analysis, CAMP: FBAT-PC analysis, Multi-marker FBATs
Archived at 2021/02/25